Pengaruh Kualitas Produk dan Harga terhadap Minat Pembelian Konsumen Gen Z pada Fore Coffee Kota Depok - Rani Kurniasari; Sofyan Marwansyah; Teni Agustina; Nurlaela Eva Puji Lestari (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The development of the coffee shop business is growing. The competitiveness between each coffee place is very intense. Generation Z is one of the targets who become coffee drinkers because of the growing lifestyle. In drinking coffee, coffee quality and price are some of the variables that Generation Z considers in their buying interest in coffee drinking. The purpose of this study is to find out the extent of the influence of product quality and price on interest in buying Fore Coffee, especially among Generation Z. This study uses a quantitative method with a survey approach. The sample consisted of Generation Z in Depok city who had made purchases at Fore Coffee, with a total of 100 respondents. Data collection was carried out through questionnaire distribution and analyzed by multiple linear regression method using SPSS. The results of the study show that product quality and price each have a positive and significant effect on purchase interest. In conclusion, determining the right product quality and price can be an effective step to increase interest in buying Fore Coffee.